Klasifikasi profil lulusan berdasarkan tracer study lulusan menggunakan algoritma Naive Bayes Classifier - Junus Sinuraya (LPPM Politeknik LP3I Medan, 2020)
The graduate profile is the role of the graduate of the study program or field of expertise / field of work planned after completing education from the study program. The determination of the profile of study program graduates is generally carried out based on the results of the assessment of stakeholder needs. Based on data from the Ministry of Research, Technology and Higher Education, the IT study program is one of the most majors or study programs in Indonesian universities and the highest number of enthusiasts choose this study program each year. Each year, graduates of IT study programs have a large number of graduates, both vocational and non-vocational colleges. The number of IT graduates is large but they have low graduate competencies, even they do not have competencies in the IT field so that their work is not in accordance with the graduate profile that has been designed. Therefore, it is necessary to conduct research to classify the profile of graduates who have worked based on tracer study data using the Naïve Bayes Classifier method. This study uses attributes, namely study program, value criteria, gender and field of work and the labels used are status (Linear and Non-Linear). The results of the study on the classification of the profile of graduates using the Naïve Bayes Classifier method show that alumni work not according to the profile of graduated by 73% and according to the profile of graduates by 23%, with a data accuracy rate of 87% and are included in the good classification category.